2018
DOI: 10.3390/cosmetics5020034
|View full text |Cite
|
Sign up to set email alerts
|

Alkenones as a Promising Green Alternative for Waxes in Cosmetics and Personal Care Products

Abstract: Abstract:The move toward green, sustainable, natural products has been growing in the cosmetic and personal care industry. Ingredients derived from marine organisms and algae are present in many cosmetic products. In this study, a new green ingredient, a wax (i.e., long-chain alkenones) derived from Isochyrsis sp., was evaluated as an alternative for cosmetic waxes. First, the melting point was determined (71.1-77.4 • C), then the alkenones' thickening capability in five emollients was evaluated and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…The determination of the yield stress is also relevant, since the lower its value the easier the product can be spread on the skin, because the yield stress determines the thickness of the product layer on the skin. Additionally, the viscosity of the LPO decreases with temperature, as it is also normal for most cosmetic and personal care products [33].…”
Section: Viscosity Studiesmentioning
confidence: 98%
“…The determination of the yield stress is also relevant, since the lower its value the easier the product can be spread on the skin, because the yield stress determines the thickness of the product layer on the skin. Additionally, the viscosity of the LPO decreases with temperature, as it is also normal for most cosmetic and personal care products [33].…”
Section: Viscosity Studiesmentioning
confidence: 98%
“…Specifically, alkenones formed a stable mix with a liquid organic UV filter, i.e., ethylhexyl methoxycinnamate, and thickened the UV filter well in that particular concentration (i.e., 10% alkenones). In the same study, alkenones created relatively low viscosity skin creams (i.e., 1470 ± 10 cP at 1 s −1 at room temperature) [23].…”
Section: Introductionmentioning
confidence: 84%
“…The alkenones used in this study have been previously described and characterized extensively [20][21][22]. In a previous study [23], we found that alkenones displayed promising properties for their potential use in sunscreens. Specifically, alkenones formed a stable mix with a liquid organic UV filter, i.e., ethylhexyl methoxycinnamate, and thickened the UV filter well in that particular concentration (i.e., 10% alkenones).…”
Section: Introductionmentioning
confidence: 96%
“…Alkenones were isolated and purified from the Isochrysis biomass as previously described [25]. In our preliminary study [14], we selected microcrystalline wax and ozokerite to compare to the alkenones. Our reasoning was the that these waxes and alkenones have similar melting points (microcrystalline wax 64-72°C [26], ozokerite 73-76°C [27], and alkenones 71.1-77.4°C [14]).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we found alkenones to be a viable alternative to microcrystalline wax and ozokerite in lipsticks and lip balms based on visual observations during a 10‐week period at two different temperatures. The goal of this study was to compare alkenones to waxes commonly used in lipsticks and instrumentally evaluate the effect of alkenones on the hardness, stiffness, firmness and pay‐off of lipsticks.…”
Section: Introductionmentioning
confidence: 99%